Accounting professors' pedagogical training: The topic under discussion - Marcos Laffin; Sonia Maria da Silva Gomes (Arizona State University, 2016)
The objective of this paper is to present the results of research that examined articles published in journals, whose subject matter was the accounting professors' pedagogical training within the Stricto Sensu postgraduate degree in accounting in Brazil. Thus, the research problem was to recognize and discuss the articles' contributions to the pedagogical training. The methodology was exploratory and the procedures involved a literature research with qualitative approach to content analysis. Based on Sacristan (1995), Brandão (2002), Santos Neto (2004), and Laffin (2005), the article presents a discussion about teaching and arguments from these authors about  the need for principles in pedagogical training for accounting professors in the Stricto Sensu postgraduate program. It appears that under the Stricto Sensu postgraduate programs in accounting the teachers' training does not assume an expression of working appropriation to teach. On the one hand, intellectual production, as a way to respond to the external evaluation, is emphasized; on the other, the ground work, under the aegis of teaching epistemology, is subsumed to the production to carry out their work.